2009
DOI: 10.1111/j.1365-2591.2009.01561.x
|View full text |Cite
|
Sign up to set email alerts
|

Endodontics or implants? A review of decisive criteria and guidelines for single tooth restorations and full arch reconstructions

Abstract: This review describes practical criteria and a systematic process to aid the treatment planning decision of whether to preserve teeth by root canal treatment (RCT) or extract and provide an implant. Recommendations presented are based on best available evidence from the literature and the expert views of specialists in endodontics and restorative dentistry, including dental implantology. A MEDLINE search was conducted using the terms 'root canal therapy', 'dental implants', 'decision making', 'treatment planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 83 publications
(208 reference statements)
0
65
0
8
Order By: Relevance
“…16 A functional period of 5 years is often needed before peri-implantitis is established and detected. 13 It has been shown that without systemic support, peri-implantitis is common. 35 Although Ruskin believes implants are superior to endodontically treated teeth due to their ability to resist dental caries, periodontal disease and structural deficiencies, implants with peri-implantitis do not seem to be very successful at resisting complications.…”
Section: Inmentioning
confidence: 99%
See 4 more Smart Citations
“…16 A functional period of 5 years is often needed before peri-implantitis is established and detected. 13 It has been shown that without systemic support, peri-implantitis is common. 35 Although Ruskin believes implants are superior to endodontically treated teeth due to their ability to resist dental caries, periodontal disease and structural deficiencies, implants with peri-implantitis do not seem to be very successful at resisting complications.…”
Section: Inmentioning
confidence: 99%
“…These can consist of implant fractures, abutment or screw loosening or fracture, loss of retention of cemented restorations or fracture of the framework. 13 Also patients who experienced an implant failure had a 30% increased risk of further failure. 41 In looking at retreatments, endodontists were more inclined to retreat a tooth and take action when a peri-apical radiolucency was noted regardless of size compared to general dentists.…”
Section: Inmentioning
confidence: 99%
See 3 more Smart Citations